E-Political Socialization, the Press and Politics - De Landtsheer, Christ´l (2014)
This book examines the state of print and electronic media in the United States of America, Europe, and China. The latest mass communication advances demonstrate that we live in an increasingly media-centric world. The chapters include theoretical and empirical studies that shed light on the meaning of this development. The trajectory of people’s move to electronic communication is a global phenomenon affecting their daily life. Does this trend aid or impede democracy? Is there an emerging digital divide contributing to an increasing gap between the rich and poor people and nations? The four parts of this book explore various aspects of political socialization and its relationship with different media, including print, broadcasting, and the Internet.